2007
DOI: 10.1248/bpb.30.266
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Expression of Bloom Helicase by Estrogenic Agents

Abstract: Carcinogenesis by 17b-estradiol (E2) is believed to be associated with its genotoxicity and stimulating activity of cell proliferation.1,2) Studies using laboratory animals 3,4) and cultured cells [5][6][7][8] showed that E2 induces tumors. E2 suppresses detoxifying enzymes, such as catalase and glutathione-S-transferase, leading to an increase in genotoxicity by E2. 9) We showed previously that E2 causes DNA damage in mammary tumor MCF-7 cells assessed by single cell gel electrophoresis, the so-called Comet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This study supported our previous conclusions 7) that estrogenic agents stimulate cell proliferation by interaction with ER and also stimulate the expression of BLM helicase participating in DNA repair during the cell cycle. However, whether this stimulation is the direct cosequence of E2 signalling affecting BLM transcription or due to an indirect effect by DNA damage induced by E2-based oxygen radicals remains to be studied.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This study supported our previous conclusions 7) that estrogenic agents stimulate cell proliferation by interaction with ER and also stimulate the expression of BLM helicase participating in DNA repair during the cell cycle. However, whether this stimulation is the direct cosequence of E2 signalling affecting BLM transcription or due to an indirect effect by DNA damage induced by E2-based oxygen radicals remains to be studied.…”
Section: Resultssupporting
confidence: 92%
“…5,6) E2 upregulates cell cycle-associated genes, especially associated with DNA synthesis, and downregulates the expression of antiproliferative and proapoptotic genes, 5) resulting collectively in the formation of mammary tumor cells and sustained proliferation. A similar effect is also observed for bisphenol A (BPA), 7) an endocrine-disrupting chemical, widely used in material for polycarbonate plastic and epoxy resin. 8) BPA has a weak estrogenic activity to stimulate cell proliferation of estrogen receptor (ER)-positive mammary tumor cells, and so is attracting considerable attention.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Iso et al (53) reported that BPA induced DNA strand breaks in ER-positive MCF-7 cells (at 1 μmol L -1 and 100 μmol L -1 ) and that its genotoxicity was ER-dependent, as evidenced by much lower effect in ER-negative MDA-MB-231 cells. The increase in DNA strand breaks was signifi cant as soon as after three hours of exposure and increased even further up to hour 24, which is in agreement with our study.…”
Section: Bisphenol-induced Dna Strand Breaks In Hepg2 Cellsmentioning
confidence: 99%
“…Such women likely have elevated estrogen levels. Estradiol(E2) has previously been found to up-regulate MCM5, suggesting participation in DNA stability during increased cell proliferation by E2 [51]. To our knowledge CDC20 has not been associated with hormones previously but could share the same qualities as MCM5.…”
Section: Members Of Cell Cycle Processes May Affect MDmentioning
confidence: 81%